HUBUNGAN ANTARA UMUR DAN JENIS KELAMIN DENGAN KEPATUHAN TERHADAP KUNJUNGAN KONTROL TEKANAN DARAH PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS PUNDONG BANTUL - Novita Kumalasari, Dian; Supatmi; Purwaningsih, Eni; Pranawati, Erma (Jurnal Riset Daerah, 2024)
As age increases, an individual's susceptibility to hypertension also rises. Individuals over the age of 60 have a higher risk of hypertension, with approximately 50-60% having blood pressure equal to or greater than 140/90 mmHg. Hypertension is more common in the elderly population. Data indicates that the prevalence of hypertension significantly increases after the age of 55, reaching 63.8% among those aged 75 and older in Indonesia. This study aims to explore and determine the relationship between age and gender with adherence to blood pressure control visits among hypertension patients in the Pundong Health Center area, Bantul. This research employs a quantitative study design with an observational analytical approach. The analysis used is the Pearson correlation test to assess the relationship between the dependent variables (age and gender) and the independent variable (adherence to visits). Data collected from 1,373 respondents at the Pundong Health Center indicate that there is no significant relationship between gender and adherence to control visits. Similarly, the results for age categories also show a P-value >0.005, indicating that age does not influence adherence to control visits among hypertension patients in Pundong. As age increases, the risk of hypertension rises, with around 50-60% of individuals over 60 experiencing high blood pressure. This study reveals that adherence to antihypertensive treatment varies based on age and gender.